Improvement of Methodical Approaches to Investigation of Anthrax Burials and Animal Burial sites - Z. F. Dugarzhapova; M. V. Chesnokova; T. А. Ivanova; S. A. Kosilko; S. V. Balakhonov (Проблемы особо опасных инфекций, 2020)
Objective - development of the unified interdepartmental approach to realization of complex epidemiological and epizootiological inspection of anthrax burials and animal refuses (AB/AR) with law compliance of standard requirements of the administrative, veterinary and sanitary-and-epidemiological legislation for solving the problems of expert estimation of object’s biological hazard, sanitary-protective zoning and rational land tenure. Materials and methods. Standard-methodical documentation and literature sources were analyzed, the official data, reference books, inventory registration and statement documents, information materials and the data of Veterinary Institutions, Rospotrebnadzor, Rosselkhoznadzor, municipal formations and other establishments were used. The data of complex epizootiological and epidemiological investigation of 27 AB/AR in five entities of Siberia and Far East over 2013-2017 were summarized. Results and discussion. For the first time the algorithm was unified and the technique of complex epidemiological and epizootiological inspections of anthrax burials (refuses) with known location was developed according to the requirements of veterinary and sanitary-and-epidemiologic rules to aid the specialists of the Rospotrebnadzor and Veterinary Science Institutions. Introduction of complex epizootiological-and-epidemiological inspection of anthrax burials (refuses) taking into account the retrospective and operative epizootiological-and-epidemiological analysis of the situation on anthrax in the Siberian administrative territory, studying of sanitary-veterinary condition of an object in aggregate with the results of laboratory examinations of samples for anthrax will permit to estimate the biological danger of anthrax burials (refuses), to solve problems of its preservation and/or utilization with the subsequent reduction of the areas of sanitary-protective zone of the object and rational land tenure.